Factor contributing to the effectiveness of online learning in the University/Hadijah Hasbi&Sharon Rinya Edwin - Hasbi, Hadijah; Edwin, Sharon Rinya (2013)
First of all, we thank to Allah s.w.t the mighty God for His blessing and consent. Without His help, we definitely won’t be able to complete this research proposal. This research proposal also would not be complete without mention of those who had helped point the way. Our sincere gratitude and deepest appreciation to our research supervisor, Madam Jennifah bt Nordin who had given constructive feedbacks, comments, guidance and valuable suggestions throughout the process of preparing this research report. We would also extend this acknowledgement to our research lecture, Madam Nadrawina bt Isnin and Dr.Hua Tee Yong from Faculty of Business of Management who willing to teach us in theoretically and SPSS. Lastly, we would like to thanks classmates that involves direct and indirectly to complete this research report ano everyone for their patience, prayers, generous help, understanding and supports that they had given us.